2015
DOI: 10.1016/j.drugpo.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Women, drugs and HIV

Abstract: Women who inject drugs are among the most vulnerable to HIV through both unsafe injections and unprotected sex. They are also among the most hidden affected populations, as they are more stigmatized than their male counterparts. Many sell sex to finance their own and their partner’s drug habit and often their partner exerts a significant amount of control over their sex work, condom use and injection practices. Women who use drugs all over the world face many different barriers to HIV service access including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 59 publications
4
125
0
5
Order By: Relevance
“…3,5 FSW who are drug-dependent or inebriated may have greater difficulty negotiating condom use or safer injection, and experiencing drug withdrawal symptoms can lead FSW to agree to clients' demands for unprotected sex. 6 As a result, HIV prevalence among FSW who inject drugs (FSW-PWID) was 12 % compared to 5 % among other FSW in these two cities. 3 Given the risks of HIV associated with injection drug use and sex work and the considerable social, economic, and medical consequences, there is a need to assess strategies that encourage or support cessation of injection as a primary goal of harm reduction for FSW-PWID.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 FSW who are drug-dependent or inebriated may have greater difficulty negotiating condom use or safer injection, and experiencing drug withdrawal symptoms can lead FSW to agree to clients' demands for unprotected sex. 6 As a result, HIV prevalence among FSW who inject drugs (FSW-PWID) was 12 % compared to 5 % among other FSW in these two cities. 3 Given the risks of HIV associated with injection drug use and sex work and the considerable social, economic, and medical consequences, there is a need to assess strategies that encourage or support cessation of injection as a primary goal of harm reduction for FSW-PWID.…”
Section: Introductionmentioning
confidence: 99%
“…By another study found that female injection drug users (IDU) in Bangladesh are at risk of a major HIV epidemic from both injection sharing and sexual risk behavior and sex worker IDU appear especially vulnerable 30 . It is also noted that eightynine percent of the respondents responded that a condom is a rubber material while 11% considered it a birth control material 30 and women who inject drugs are among the most vulnerable to HIV through both unsafe injections and unprotected sex [31][32] . On the other hand, all over the world, HIV is very much concerning one of the issues but then rural men have lacking about the knowledge and prevention of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…17,23 In countries in which drug or alcohol use among women is a cultural taboo, FSWs may feel pressured to hide their substance use, which may discourage women from accessing services. 31 Underlying these stigmas, the social organization of gender and power promotes gender inequalities and norms supporting GBV, which may heighten FSWs’ vulnerability to HIV/STIs. 32 …”
Section: Risk Environments For Fswsmentioning
confidence: 99%
“…34 Because most FSWs have children who are major influences on their lives, consideration should be made for how to integrate their reproductive health and family needs with HIV prevention and enhance FSWs’ parenting skills so that their children are not apprehended by authorities. 31,35 …”
Section: Risk Environments For Fswsmentioning
confidence: 99%